THE ROLE OF LOCAL GOVERNMENTS IN EMPOWERING FARMERS IN DOGIYAI REGENCY - Giofani Inge Aria H; Supardal (Bajang Institute, 2022)
Natural potential in agriculture has a very important role in meeting the food needs of the community, but due to the lack of empowerment of human resources, not all farmers can take advantage of the existing natural potential. For this reason, the role of the Department of Agriculture and Plantation of Dogiyai Regency is needed in community empowerment in the agricultural sector so that human resources can be empowered to manage the existing natural potential. The research method used in this research is qualitative research with data collection techniques using three ways, namely observation, interviews and documentation.Data analysis techniques used include: data collection, data reduction, data presentation, and drawing conclusions.The results of the study show that the empowerment program in the form of: a) Training and Coaching, b) Providing Counseling and Mentoring, and c) Providing Facilities and Infrastructure, has been running quite well but for now it is still hampered due to the Covid-19 outbreak.The inhibiting and supporting factors in the empowerment process carried out by the Department of Agriculture and plantations on farmers are Supporting Factors, in the form of: a) The existence of farmer groups, and b) The existence of community participation. Inhibiting factors, in the form of: a) Lack of agricultural extension experts, b) Lack of the next generation of agriculture, and c) Lack of clear institutions